Takotsubo cardiomyopathy in pregnancy: A focused review - Heena Garg; Shashi Singh; Rashmi Ramachandran; Anjan Trikha (Wolters Kluwer Medknow Publications, 2023)
Takotsubo cardiomyopathy (TTCM) has been described as a new entity of cardiomyopathy at the turn of the century. Takotsubo, a Japanese word, denotes an "octopus pot," a fishing jar that has a narrow neck and wide base for trapping an octopus. This correlates with the shape of the heart on left ventriculography with apical ballooning and basal hypokinesia. The first case was defined in 1990 by Sato et al. and a plethora of literature exists about TTCM ever since. While believed to be an occurrence in elderly postmenopausal females, various reports have been found in recent literature highlighting its occurrence during the antenatal, perinatal, and postpartum periods. It is high time that TTCM is kept in the purview of diagnosing acute cardiopulmonary symptoms in pregnancy. Only an accurate and timely diagnosis of TTCM in pregnancy can lead to an early intervention and prevent countless morbidities and mortalities. A multidisciplinary approach with psychological rehabilitation is recommended to prevent recurrence. We present a concise review of the diagnosis, clinical features and management of this condition and the salient differentiating features from peripartum cardiomyopathy (PPCM). We found 26 cases of TTCM and 16 cases of reverse TTCM. There is a void in knowledge about estrogen levels and the corresponding levels of catecholamines in due course of pregnancy. Future studies to correlate between declining estrogen levels and catecholamine levels at the onset of symptoms of TTCM need to be done to get more insights into this phenomenon.